2016
DOI: 10.7895/ijadr.v5i2.222
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Use Disorders Identification Test (AUDIT): A review of graded severity algorithms and national adaptations

Abstract: Aims: Since it was first released in 1989, the Alcohol Use Disorders Identification Test (AUDIT) has generated a large amount of research to evaluate its psychometric properties. The purpose of this review is to critically evaluate the literature relevant to applications of the AUDIT in screening, brief intervention, and treatment referral programs, and identify national adaptations of the AUDIT to country-specific health, education, and reimbursement needs. Methods:Methods comprised a search of the world lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 51 publications
(61 reference statements)
2
55
1
4
Order By: Relevance
“…Education level was ranked into five groups: insufficient school (including illiterates, people who never attended school or people who did not complete elementary school I), elementary school II (incomplete or complete), intermediate school (incomplete or complete), and higher education (incomplete or complete). The Alcohol Use Disorder Identification Test (AUDIT) was used to rank the pattern of alcohol use into four risk zones: (I) non-drinker, (II) non-hazardous, (III) hazardous and (IV) harmful drinking (Babor & Robaina, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Education level was ranked into five groups: insufficient school (including illiterates, people who never attended school or people who did not complete elementary school I), elementary school II (incomplete or complete), intermediate school (incomplete or complete), and higher education (incomplete or complete). The Alcohol Use Disorder Identification Test (AUDIT) was used to rank the pattern of alcohol use into four risk zones: (I) non-drinker, (II) non-hazardous, (III) hazardous and (IV) harmful drinking (Babor & Robaina, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, all participants needed to report a stable pattern of moderate, non-risky alcohol consumption habits. This was defined as Alcohol Use Disorders Identification Test (AUDIT) scores between 1 and 15 points [50], and reporting to binge drink (i.e., consume eight or more standard units of alcohol on a single occasion/ evening) no more than once a month and no less than once a year. Women were not permitted to participate in the study due to the potential risk of undetected pregnancy.…”
Section: Participantsmentioning
confidence: 99%
“…In 1982, the World Health Organization (WHO) began to develop an international screening test for hazardous and harmful drinkers, and to evaluate how these patients could be managed in primary health-care settings [6]. That project produced the Alcohol Use Disorders Identification Test (AUDIT), which has become the most widely used alcohol screening test in the world, in part because of an impressive science base that now includes more than 350 scientific papers [7]. The validation work for the AUDIT was followed by a 10-nation study to test the effectiveness of brief intervention (BI) [8], which showed that clinically meaningful changes in patients' drinking behavior could be produced with a small investment of time and clinical resources.…”
Section: A Brief History Of Sbirtmentioning
confidence: 99%